2019
DOI: 10.1159/000498897
|View full text |Cite
|
Sign up to set email alerts
|

Renovascular Hypertension Aggravates Atherosclerosis in Cholesterol-Fed Rabbits

Abstract: Background: Hypertension is a major risk factor for atherosclerotic disease. However, it is still not clear whether mechanical stress caused by hypertension directly affects the atherosclerotic development in the aorta and coronary arteries. Objectives and Methods: We generated a hypertensive (HTN) rabbit model by surgical removal of the left kidney and partial ligation of the right renal artery. After a 16-week cholesterol diet, we compared aortic and coronary atherosclerosis of HTN rabbits with those of norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…A number of pathophysiologic pathways are shared by both disorders. Endothelial dysfunction, which aggravates atherosclerosis and makes atherosclerotic plaques more unstable, is caused by hypertension [ 32 , 33 , 34 ]. Several studies on lycopene supplementation have showed promising results in lowering blood pressure and coronary artery disease [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…A number of pathophysiologic pathways are shared by both disorders. Endothelial dysfunction, which aggravates atherosclerosis and makes atherosclerotic plaques more unstable, is caused by hypertension [ 32 , 33 , 34 ]. Several studies on lycopene supplementation have showed promising results in lowering blood pressure and coronary artery disease [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…ApoE KO and WT NZW rabbits aged 7 months (6 males and females for both groups) were fed a cholesterol diet for 16 weeks. The cholesterol diet used for this experiment was composed of the normal standard diet (17% protein, 4% fat, and 14% crude fiber) (CLEA Japan, Inc, Tokyo, Japan), which was supplemented with 0.3% cholesterol and 3% soybean oil, which did not affect the body weight ( 27 ). These two models exhibited hypercholesterolemia due to the accumulation of plasma remnant lipoproteins (β-VLDLs) ( 28 ).…”
Section: Methodsmentioning
confidence: 99%
“…Using these three models, we investigated whether different types of hypercholesterolemia exert different effects on the development of cerebral atherosclerosis. Furthermore, we examined cerebral atherosclerosis in hypertensive WHHL rabbits induced by 1K1C (surgical removal of the left kidney and partial ligation of the right renal artery) methods, as reported in previous studies ( 26 , 27 ). All animal experiments were performed according to the approval of the Animal Care Committee of the University of Yamanashi and conformed to the Guide for the Care and Use of Laboratory Animals published by the US National Institutes of Health.…”
Section: Methodsmentioning
confidence: 99%
“…These results indicated that hypertension not only enhances the development of atherosclerosis but also promotes plaque rupture that leads to cardiac death [ 63 ], a phenomenon that is rarely seen in mouse models. Another study also reprised the effect of hypertension on atherosclerosis by showing that hypertension promotes atherosclerosis in large arteries and also affects arteriolosclerosis in small arteries independent of lipid and apolipoprotein levels in plasma [ 64 ].…”
Section: Animal Models Of Atherosclerosismentioning
confidence: 99%